Physiological Dose-Response of Coffee (Coffea arabica L.) Plants to Glyphosate Depends on Growth Stage - de Carvalho,Leonardo Bianco (Instituto de Investigaciones Agropecuarias, INIA, 2012)
Glyphosate is the main herbicide used in coffee (Coffea arabica L.) plantations in Brazil. Problems with herbicide drift commonly occur in orchard fields due to non-adequate spraying conditions. A series of experiments was carried out aiming to evaluate physiological dose-response of C. arabica plants submitted to exposure to simulated glyphosate drift in two distinct plant growth stages. Glyphosate was applied at 0, 180, 360, and 720 g acid equivalent (AE) ha-1 directly on coffee plants with 10 and 45 d after transplanting (DAT). Glyphosate doses in a range of 180-360 g AE ha-1 increased photosynthesis, transpiration and stomatal conductance in 10 DAT-plants up to 14 d after application (DAA) while, in 45 DAT-plants, an increase was observed only up to 2 DAA, but this pattern was not persistent afterwards so that no difference in gas exchange was observed at 60 DAA in both plants. Macronutrient content was not affected by glyphosate application in both plants. Plant DM accumulation was not affected by glyphosate application at 10 DAT-plants, but an increase in plant growth was observed when glyphosate was applied in a range of 360-720 g AE ha-1 in 45 DAT-plants. Coffea arabica cv. Catuaí Vermelho IAC-144 responded differentially to glyphosate drift depending on plant growth stage, regarding on photosynthesis, transpiration, stomatal conductance, and plant growth, in spite of macronutrient nutrition was not affected.